Other worlds : society seen through soap opera - Anger, Dorothy C. (Dorothy Catherine), 1954- (CEL - Canadian Publishers Collection., 1999)
When American nation-wide network radio was still in its infancy, new programs such as Ma Perkins began to feature ongoing story lines in fifteen minute episodes focusing on home life and romance. Procter & Gamble and other soap companies were the most common sponsors, and soon the genre of soap opera had been christened. In this entertaining but probing inquiry into the nature, history, and significance of the soaps, anthropologist Dorothy Anger shows how they reflect and shape the ethos of particular nations. Anger's primary focus is on the similarities and contrasts between American soaps and British serials such as Coronation Street and EastEnders-soaps that look more like ordinary life than do their American couterparts, and that feature story-lines based on surviving on what you can earn rather than striving for more. Anger looks at the industry as well as the televised product and examines the social effects as well as the inherent characteristics of soaps-with particular emphasis placed on the ways in which their implicit messages reflect and reinforce the ethos of the society in which they are made. She examines how the soaps themselves are shaped in turn by the cultures and the place from which they come. Though far from uncritical of the genre, Anger herself loves the soaps. She recognizes how soap operas provide a "continuing renewal of the familiar." Through interviews with and observations of soap fans she shows that the sharing of information and opinion after the program is over is as important to the viewers as actually following the stories. Informed by recent work in anthropology and cultural theory, Other Worlds will easily be accessible to a general as well as an academic audience. -- Provided by publisher